‘Microphone off’ – application of the process model of interpreting to the classroom - Kalina, Sylvia (Kalbotyra, 2007)
In the initial period when simultaneous conference interpreting developed into a profession, an excellent conference interpreter (CI) was a gifted person who had an excellent command of his/her working languages (in general, not more than three) and a broad knowledge of the world, talent, persistence and aptitude –the latter were not specified in any great detail. With these gifts, a person should find it easy to become an accomplished CI. What such a person needed was abundant field practice. [...]